The Influence of Marketing Mix on Laptop Purchasing Decisions (Study at One's Computer Store in Krueng Geukuh, North Aceh Regency) - Muliana, Muliana; Ameliany, Nanda; Nursanjaya, Nursanjaya; Iryani, Lisa; Ritonga, Nursakinah (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
One's Computer shop is a shop that sells various kinds of laptops and other laptop equipment. This study aims to determine the effect of marketing mix on laptop purchasing decisions at One's Computer stores in Krueng Geukuh, North Aceh Regency. This study uses descriptive quantitative research methods and obtained 97 respondents as a research sample obtained from the Lemesshaw formula. The data analysis method used in this study is simple regression analysis, instrument test, classical assumption test and hypothesis testing and the coefficient of determination with the help of the SPSS 20.0 program. The results of data processing that has been done previously show that the Ha hypothesis is accepted. Through the t-test with a 5% error rate (a=0.05), the value of Thitung is 19.079 and the value of Ttabel is 1.986 so that (19.079> 1.986) or a sig of 0.000 <0.05. So it can be concluded that the Marketing Mix variable (X) has a positive and significant effect on the Purchasing Decision variable (Y) at the One's Computer Store in Krueng Geukuh, North Aceh Regency. Based on the research that has been done, it means that consumers think that the One's Computer store implements the marketing mix well so that it can improve purchasing decisions.